Sanksi Pidana Terhadap Anggota TNI dalam Perspektif Keadilan Berdasarkan Pasal 363 Ayat (1) KUHP (Studi Putusan No.126-K/PM.II-08/AD/VII/2020) - Rahmadani Husni; R. Rahaditya (LPPM Universitas Ekasakti Padang, 2023)
Criminal acts of theft that occur in Indonesia are not only committed by the general public, there are also thefts committed by several elements of the state apparatus, such as theft committed by members of the Indonesian National Army (TNI). If during the term of office a member of the TNI carries out activities against the law or this is related to a criminal act, the Military Police have the authority to carry out the inquiry and investigation process in accordance with the applicable rules and SOPs in the Criminal Procedure Code (KUHAP) and the Law. -Law Number 31 of 1997 concerning Military Justice. In Article 69 paragraph (1) of Law no. 31 of 1997. Normative research is used by the author because it applies legal theories and positive legal regulations in analyzing legal criminal sanctions. Meanwhile, the results obtained from this writing are that the main criminal sanction is imprisonment, and additional criminal sanctions are in the form of dismissal.